2017
DOI: 10.12973/eurasia.2017.00833a
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and Learning Science Outdoors in Schools’ Immediate Surroundings at K-12 Levels: A Meta-Synthesis

Abstract: This literature review synthesizes empirical data of 18 articles published between 2000 and 2015 about teaching and learning science outdoors from kindergarten to secondary levels (K-12). We asked four questions: (1) What are the general characteristics of the corpus of studies on teaching and learning science outdoors in schools' immediate surroundings at K-12 levels? (2) What are the authors' aims for conducting studies about teaching and learning science outdoors? (3) What are the main outcomes related to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
10

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 25 publications
3
39
0
10
Order By: Relevance
“…Learning requires a lot of work and activities (Yıldırım & Akamca, 2017). In addition, Gair (1997) cited in (Yıldırım & Akamca, 2017;Ayotte-Beaudet et al, 2017;Dillon et al, 2017) listed six features of an outdoor education programme: 1) Education occurs outdoor. It does not have to be offered in a classroom.…”
Section: A Coaching Effort Aimed At Children From Birth Until the Agementioning
confidence: 99%
“…Learning requires a lot of work and activities (Yıldırım & Akamca, 2017). In addition, Gair (1997) cited in (Yıldırım & Akamca, 2017;Ayotte-Beaudet et al, 2017;Dillon et al, 2017) listed six features of an outdoor education programme: 1) Education occurs outdoor. It does not have to be offered in a classroom.…”
Section: A Coaching Effort Aimed At Children From Birth Until the Agementioning
confidence: 99%
“…Results obtained through these studies have shown that it is not only students who benefit from such programmes, as teachers also gain sensitivity towards the environment and consider this form of learning to have a greater impact than learning carried out indoors. [30,31]. Nevertheless, the same studies point to a lack of time and sufficient budgets, together with officially imposed curriculums as the main drawbacks for these activities.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, educational institutions have realized that museums are ideal educational settings that can support active learning [18]. Studies in the field of outdoor education also conclude that such learning environments could positively influence students' knowledge, attitudes, interests, or motivation [19][20][21].…”
Section: Introductionmentioning
confidence: 99%